Community involvement - it can be done - P.O Sills (AOSIS, 1981)
In the course of their work the community nurses of Brakpan became aware of a large number of elderly people for whom there were few services available. Health Year (1979) gave rise to the idea of developing a project for the elderly in the community, with the prime objective of promoting their participation in and involvement with their own affairs.